Evaluasi Drug Related Problems (DRPs) Antibiotik pada Pasien Sepsis di Rumah Sakit di Yogyakarta - SAMUEL BUDI; ZULLIES IKAWATI; IWAN DWIPRAHASTO; TITIK NURYASTUTI (JURNAL ILMU KEFARMASIAN INDONESIA, 2017)
Sepsis is a manifestation of the most severe acute infections that can lead to the various organ failure generally ends with death in 30-50% of cases. The number of sepsis deaths in developed countries can be reduced to 11-15%, but in developing countries it was reported above 45%. Proper and adequate use of empirical antibiotics may decrease the risk of death in sepsis and may at least shorten patient duration of care in the hospital. Aim to this study was determine the pattern of antibiotic use, the incidence of Drug Related Problems (DRPs) and clinical outcomes in septic patients in hospital X at Yogyakarta. An observational study was carried out during the period of January-December 2015 in hospital X at Yogyakarta. Data were collected retrospectively among patients with sepsis, age > 15 years old, hospitalized during the the study period. From 632 cases, 162 patients were diagnosed as sepsis and met the inclusion criteria of the study. The antibiotics used were cephalosporin (42.58%), quinolone (17.46%), carbapenem (10.77%), aminoglycoside (9.33%), imidazole (8.85%) and macrolide (4.88%). Poor clinical outcomes associated with DRPs (64.29%) were greater than those that showed good clinical outcomes (35.71%). The incidence of DRPs in sepsis treatment is still high (60.49%), and is generally associated with antibiotic needs, the inappropriate selection of antibiotics, inadequate dosage and the presence of antibiotic interactions.